Output energy maximization of a single axis photovoltaic solar tracking system: experimental verification - Shin-Horng Chong; N. N. Chandren; C. R. Allan Soon (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Major depletion of fossil fuel and the increase of greenhouse gasses such as carbon dioxide, chloroflurocarbons (CFCs), hydroflurocarbon (HFCs), perflurocarbons (PFCs) and Sulphur hexafluoride (SF6) worldwide are the catalyst for the interest of many counties towards renewable energy. The rising cost of electricity due to higher demand and less resource also led to the renewable energy venture. One of the most famous renewable energy is solar energy. Unfortunately, renewable energies are dependent on environment conditions, too. One of the major problems that affect the output energy of the solar panel is the cloud shadowing problem. Photovoltaic solar and wind hybrid system is capable to reduce the effects of the cloud shadowing by harvesting two different energy resources. However, the availability of wind energy harvesting has shown its instability performance. In this work, the photovoltaic solar array of the laboratory-scale single axis solar tracking system to maximize the output energy of the solar panel is examined experimentally. The solar array is connected in series and parallel configurations, and is experimented under different partical-shadowed conditions. The experimentation is done to develop a solar array that has a minimum effect towards this type of occurances. Experimental results proved that the parallel configured solar panel has showed less influence by the cloud shadowing as compared to the single one.